Age- and sex-standardized prevalence of alcohol consumption and its determinants in the western region of Iran, Ilam: a cross-sectional study - Arezoo Sarmad; Dilan Ahmadzadeh; Mohammad Bazyar; Kamran Malekan; Zahra Malekan; Reza Pakzad (BMC Public Health)
Abstract Background and objective In recent years, alcohol consumption in different parts of Iran has increased. However, this growth was dramatic in deprived regions. The percent study aimed to determine the age-sex standardized prevalence of alcohol consumption and related factors in the general population of Ilam city during 2021–2022. Method This population-based cross-sectional study was conducted in the general population of Ilam city located in western Iran. A total of 1,431 individuals over the age of 15 were included in the study using multi-stage cluster sampling. Alcohol consumption was assessed using a Persian version of high-risk behavior questionnaire (Cronbach’s alpha > 73%). Analysis was done by Stata version 11 and R Software. Logistic regression analysis was used for data analysis and calculating odds ratio (OR), and a significance level of 0.05 was considered. Results In total 1,431 individuals completed the questionnaire. The mean ± standard deviation (SD) age of the study participants was 43.40 ± 15.51 years. The age-sex standardized prevalence with 95% confidence interval (CI) of alcohol consumption was 4.05% (95% CI: 3.09 to 5.20). Based on multiple logistic model, having a bachelor’s degree (OR: 7.13; 95% CI: 1.89 to 26.76), cigarette smoking (OR: 6.92; 95% CI: 2.94 to 16.29), hookah smoking (OR: 7.34; 95% CI: 3.09 to 17.47) and drug abuse (OR: 2.88; 95% CI: 1.38 to 5.99) had a positive association with alcohol consumption. Furthermore, having a high economic status 0.62 (OR: 0.62; 95% CI: 0.26 to 1.48) had a negative association with alcohol consumption. The most powerful determinants (according to standardized coefficient) for alcohol consumption were hookah smoking (standardized coefficient: 0.588) and high education level (0.743). Conclusion Considering the prevalence of alcohol consumption in the population over 15 years old, it is necessary to take preventive and intervention measures, with more attention from health policymakers and other sectors.